2010
DOI: 10.1016/j.amjsurg.2009.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors and patterns of recurrence in esophageal cancer assert arguments for extended two-field transthoracic esophagectomy

Abstract: Radicality and LN ratio are strong prognostic factors. High radicality and adequate nodal assessment are guaranteed by an extended transthoracic approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
39
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 26 publications
7
39
0
Order By: Relevance
“…Evidence demonstrated that there is a negative association between overall survival and lymph node ratio in N1 patients, and where different cut-off values were investigated, a ratio greater than 20% was frequently associated with poor overall survival in numerous studies. Similar results for lymph node ratio were also noted in other malignancies, such as gastric, oesophageal and colorectal cancers, [33][34][35] where it is a well-established independent prognostic factor for overall survival. 33 A systematic review by Ceelen et al on lymph node ratio in stage III colorectal cancer confirmed a hazard ratio for overall survival of 2.36 (95% confidence interval 2.14-2.61).…”
Section: Discussionsupporting
confidence: 66%
“…Evidence demonstrated that there is a negative association between overall survival and lymph node ratio in N1 patients, and where different cut-off values were investigated, a ratio greater than 20% was frequently associated with poor overall survival in numerous studies. Similar results for lymph node ratio were also noted in other malignancies, such as gastric, oesophageal and colorectal cancers, [33][34][35] where it is a well-established independent prognostic factor for overall survival. 33 A systematic review by Ceelen et al on lymph node ratio in stage III colorectal cancer confirmed a hazard ratio for overall survival of 2.36 (95% confidence interval 2.14-2.61).…”
Section: Discussionsupporting
confidence: 66%
“…In turn, we have verified that our results concur with those from more extensive series published at international level (8,9,13,14).…”
Section: Discussionsupporting
confidence: 82%
“…The majority of the studies analysed (5,6,(8)(9)(10)(11)(12)(13)(14)16) have found that the degree of tumour invasion, as well as the presence of metastatic lymph, are variables that are asso- ciated with the recurrence of the disease, and similarly, in our study the patients with higher stages had a higher probability of recurrence.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Isolated recurrence was defined as a situation with no evidence of metachronous recurrence within 6 weeks. If a second recurrence was confirmed within 6 weeks of the first, it was deemed synchronous10.…”
Section: Methodsmentioning
confidence: 99%